SECO-RCR: A Tool to Manage Requirements Change in Software Ecosystems - Gonçalves, Eduardo dos Santos; Malcher, Paulo; Moraes, Laura O.; Viana, Davi; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3606, 2024)
Software ecosystems (SECO) are becoming a predominant mode of modern software development and can be defined from different perspectives. From a project perspective, SECO are groups of projects that are developed and co-evolved in the same environment. SECO introduced complexity into requirements management, which is a key process of requirements engineering (RE) and an effective way to ensure software quality. There is difficulty in managing requirements change in open and dynamic environments such as SECO due to the existence of multiple stakeholders that can form distinct crowds in the ecosystem. In SECO, a crowd is a large and heterogeneous user base that provides requirements through multiple communication channels. Hence, meeting the expectations of distinct crowds in SECO requires new RE approaches. This paper presents a tool called Software Ecosystems - Requirements Change Request (SECO-RCR) that applies software repository mining, natural language processing techniques, and machine learning to support requirements change management in SECO. SECO-RCR allows requirements managers to define different RCR and consult different crowds to assist them in their decision making. Apresentação (Youtube):  https://youtu.be/2OgCRvrA1Ec